Valuation of carbon sequestration by poplar based agroforestry systems in Yamunanagar, Haryana - RIZVI, R H; SINGH, MAHENDRA; KUMAR, ANIL; SRIVASTAVA, SHEFALI (The Indian Journal of Agricultural Sciences, 2020)
Poplar (Populus deltoides) based agroforestry systems in Yamunanagar district of Haryana have great potential for carbon sequestration, which is considered as an ecosystems service. This study bridges the knowledge gap regarding payment for ecosystem services through carbon sequestration by poplar farmers. This study was conducted in year 2018 with the objective of estimating the quantity and value of carbon sequestered by poplar based agroforestry systems. Remote sensing analysis for year 2017 revealed that poplar is dominant tree species grown by farmers on their field and occupied about 13.97% of district’s geographical area. Timber production of poplar trees was estimated at 45.9 and 113.3 t/ha for seven years of rotation in boundary and agrisilviculture systems, respectively. The CO2 sequestered by poplar trees in boundary and agrisilviculture systems come out to be 99.2 and 242.0 tCO2 e for seven year-old plantation, and total value of this carbon sequestered was estimated at US$ 1778 and 4673 @US$ 5.1/t CO2e for seven years of rotation, respectively. At district level, estimated value for carbon sequestered by poplar based agroforestry systems was amounted to US$ 25.43 million @US$ 5.1/t CO2 e for entire rotation period of seven years in an area of 172506.96 ha. At country level, this ecosystem service of carbon sequestration would yield hefty amount of about US$ 285 million (`₹185 billion). Hence, poplar based agroforestry systems in India are sustainable solution for not only climate change mitigation but can also enhance farmers’ income through payment of ecosystems service.